Retención y pago de tributos de la empresa comercial "Saul Litardo" año 2010 - Mena Chacha, José Alexander (2012)
The present Work of Investigation was carried out to the Commercial one "Saúl Litardo", it is a business that sells products of more and smaller massive consumption, under the condition of taking accounting, and he/she has as tributary obligations, to retain for the made purchases, I pay monthly of IVA, Tax to the Rent, Advance of Tax to the Rent, Transactional Annexes. The reason to develop the Work of Investigation, of this Company is to verify the execution of its tributary obligations, and to detect the possible contingencies that can exist, eats a bad interpretation of the law for example, among other, considering that the tributary administration, has constant upgrades. The Taxpaying Emilio Saúl Litardo Valverde, it has fulfilled all their tributary obligations appropriately, it shows of it, it is that he/she has never paid, interest and tickets for their declarations, neither he/she has had notifications for sanctions, in a same way the Annexed Reoc is presented in the established time. The Expenses are always according to their revenues, what allows to maintain a margin of utility and reasonable liquidity. As much in Accounting as in Tribute, alone he/she has registered in their Annexes, the bill Box and Inventory, when it should also register their properties, vehicles and office teams. To conclude the Taxpaying EMILIO SAÚL LITARDO VALVERDE, he/she will carry out their declarations applying the percentage corresponding of tributary credit and it will register the salary increment in the Ecuadorian Institute of Social security, apart from this, everything very well, respecting the normative point of the S.R.I., as those of the I.E.S.S.